Towards integrated sustainable biofuel and chemical production: An application of banana pseudostem ash in the production of biodiesel and recovery of lignin from bamboo leaves. (February 2023) - Daimary, Niran; Eldiehy, Khalifa S.H.; Bora, Neelam; Boruah, Pankaj; Rather, Muzamil Ahmad; Mandal, Manabendra; Bora, Utpal; Deka, Dhanapati
Abstract: This study investigated an integrated approach to the biowaste transformation and valorization of byproducts. Biochar obtained from the banana pseudostem was calcined to synthesize a heterogeneous catalyst and sustainably prepare a highly alkaline solution. The ash was utilized directly as a heterogeneous catalyst in biodiesel production from waste cooking oil. At the same time, an alkaline solution prepared from the ash was used for delignification and recovery of lignin from bamboo leaves by the hydrothermal reaction. Techniques like Fourier-transform infrared spectroscopy (FTIR), Field emission scanning electron microscopy (FESEM), Brunauer-Emmett-Teller (BET), Transmission electron microscopy (TEM), and Energy dispersive X-ray (EDX) were applied to characterized the catalyst. The alkaline solution was analyzed with Atomic absorption spectroscopy (AAS). The Response surface methodology (RSM) technique was considered for the optimization of different parameters in the transesterification and hydrothermal reaction. Under the optimized condition, waste cooking oil (WCO) to Fatty acid methyl ester (FAME) conversion was 97.56 ± 0.11%, and lignin recovery was 43.20 ± 0.45%. While at the best operating pyrolysis temperature, the liquid fraction yield from the banana pseudostem (500 °C) was 38.10 ± 0.31 wt%. This integrated study approach encourages the inexpensive, sustainable, and environment-friendly pathway for synthesizing catalysts and preparing a highly alkaline solution for the valorization of biowaste into biofuel and biochemicals. Graphical abstract: Image 1 Highlights: Sustainably banana pseudostem, bamboo leaves, and waste cooking oil were valorized. When biochar (BSBC) is calcined at 700 °C, it transforms into mixed metal oxide. Calcinated biochar ash exhibits high alkalinity when it is mixed with water. 43.20% of lignin was recovered from bamboo leaves using an ash alkaline solution. When ash was used as a catalyst, 97.56% of FAME conversion was achieved.